2009
DOI: 10.3390/ijerph6020654
|View full text |Cite
|
Sign up to set email alerts
|

Small Area and Individual Level Predictors of Physical Activity in Urban Communities: A Multi-Level Study in Stoke on Trent, England

Abstract: Reducing population physical inactivity has been declared a global public health priority. We report a detailed multi-level analysis of small area indices and individual factors as correlates of physical activity in deprived urban areas. Multi-level regression analysis was used to investigate environmental and individual correlates of physical activity. Nine individual factors were retained in the overall model, two related to individual intentions or beliefs, three to access to shops, work or fast food outlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 41 publications
1
27
1
1
Order By: Relevance
“…It is reasonable therefore, to assume that the mechanisms linking obesity and area level deprivation reflect the underlying effects of deprivation on dietary habits and physical activity status. Evidence suggests that the deprivation of an area is associated with characteristics of the food (43)(44)(45)(46)(47) and physical activity environment (43,45,(48)(49)(50), with more deprived areas thought to be more obesogenic (51). Of further interest is that fact that the relationship between obesity and SES is stronger, and in many cases only shown to be statistically significant in girls.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable therefore, to assume that the mechanisms linking obesity and area level deprivation reflect the underlying effects of deprivation on dietary habits and physical activity status. Evidence suggests that the deprivation of an area is associated with characteristics of the food (43)(44)(45)(46)(47) and physical activity environment (43,45,(48)(49)(50), with more deprived areas thought to be more obesogenic (51). Of further interest is that fact that the relationship between obesity and SES is stronger, and in many cases only shown to be statistically significant in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in multiple countries have demonstrated that recreational walking, increased physical activity and reduced sedentary time were associated with access to, and use of green space in working age adults, children and senior citizens (Epstein et al 2006;Kaczynski and Henderson 2007;Kaczynski et al 2008;Sugiyama and Ward Thompson 2008;Cochrane et al 2009;Almanza et al 2012;Lachowycz et al 2012;Astell-Burt et al 2013;Schipperijn et al 2013;Lachowycz and Jones 2014;Sugiyama et al 2014;Gardsjord et al 2014;James et al 2015;Sallis et al 2016). Almanza et al (2012) used satellite images and GPS and accelerometer data from children in several communities in California, the United States to demonstrate that increased residential greenness was positively associated with moderate to vigorous physical activity.…”
Section: Enhanced Physical Activity and Improved Fitnessmentioning
confidence: 99%
“…Individual factors, such as motivation to engage in outdoor activities or orientation towards nature, may be equally very strong drivers of park visitation behavior [24], [25]. In this case, it is an individual's orientation , rather than opportunity alone, that may determine the motivation to spend time in urban green space.…”
Section: Introductionmentioning
confidence: 99%